(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ هذا البحث لدراسة تأثير رش أربعة مصادر للزنك هي: كبريتات الزنك، كربونات الزنك، فوسفات الزنك، شيلات الزنك، في مرحلة الإزهار على بعض دلائل النمو لنبات القطن، استخدم تركيز منفرد 1% لكل مصدر من المصادر المدروسة إضافة إلى الشاهد بدون رش. صممت التجربة بالطريقة العشوائية الكاملة في أربع مكررات بينت الدراسة ما يلي: أدى الرش بمصادر مختلفة للزنك إلى زيادة معنوية في المحصول البيولوجي، ووزن المادة الجافة، ودليل المساحة الورقية، والمساحة النسبية للأوراق، وفترة بقاء الأوراق بكفاءتها، ومعدل نمو المحصولي، والكفاءة التمثيلية، والإنتاجية ( كغ/هـ)، ودرجة الإنتاجية مقارنة مع الشاهد. أعطى الرش بكبريتات وشيلات الزنك أفضل القيم المذكورة أعلاه مقارنة مع مصدري الزنك الأخريين وتفوقا معنوياً في دليل المساحة الورقية، والمساحة النسبية للأوراق والإنتاجية. This work was carried out to study the effect of spraying 4 sources of Zink, viz., ZnSO4, ZnCO3, Zn (PO4)2 and Zn EDTA, at flowering stage, on some growth parameters of cotton plant. Single concentration (1%) was used for each source of the zinc sources studied, including control treatment. A randomized complete block design (RCBD), with four replicates, was used. Results showed that spraying different sources of zinc significantly increased biological yield, dry weight, leaf area index, leaf area ratio, leaf area duration, crop growth rate, net assimilation rate, productivity and productivity score as compared to the control. Also, spraying ZnSO4 and Zn EDTA gave the best results compared to the rest of the sources in respect to the leaf area index, leaf area ratio, and productivity.